Od wymazania do zapomnienia (i co dalej?) – casus Palestra - Dzierżanowski, Lech (Res Facta Nova, 2025)
The case of Roman Palester shows how, in the 20th century, the figure of a promising composer could in practice be erased for political reasons. Born in Śniatyn (Galicia) in 1907 and educated during the Second Polish Republic, Palester was one of the most interestingly developing Polish composers of his time. Also very prolific during the Second World War, Palester was actively involved in rebuilding musical life in the first post-war years. However, when his stay in Paris turned into emigration, Palester was expelled from the ZKP and subsequently erased from the annals of Polish music history. His association with Polish émigré centres: the radio station Radio Free Europe and ‘Kultura Paryska’ ultimately closed the composer’s path to return to the stage in Poland (with the exception of a brief episode of the thaw of 1957–1959). The article describes this case with particular attention to the difficulties involved in changing this situation after the change of the political system and the composer’s death. Although new editions and recordings of his works have appeared since the composer’s death, as well as a comprehensive monograph by Zofia Helman, knowledge of Palester remains limited to this day. The author examines the prospects for bringing back to concert stages the work of this, one of the most interesting figures in the world of 20th century Polish music.